Longitudinal Analysis of Persistent Postconcussion Symptoms, Probable TBI, and Intimate Partner Violence Perpetration Among Veterans. Issue 1 (January 2022) - Portnoy, Galina A.; Relyea, Mark R.; Presseau, Candice; Orazietti, Skye; Martino, Steve; Brandt, Cynthia A.; Haskell, Sally G.
Abstract : Objective: To determine veterans' intimate partner violence (IPV) perpetration following report of traumatic brain injury (TBI) and persistent postconcussion symptoms (PPCSs). Setting: Five Department of Veterans Affairs (VA) medical centers. Participants: Veterans with nonmissing data on main measures, resulting in N = 1150 at baseline and N = 827 at follow-up. Design: Prospective cohort study with secondary data analysis of self-reported TBI, PPCSs, and IPV perpetration, controlling for common predictors of IPV, including binge drinking, marijuana use, pain intensity, and probable posttraumatic stress disorder. Main Measures: VA TBI Screening Tool to assess for probable TBI and PPCSs; Conflict Tactics Scale-Revised (CTS-2S) to assess for IPV perpetration. Results: Almost half (48%) of participants reported IPV perpetration at follow-up. Both probable TBI and higher PPCSs at baseline were associated with overall IPV perpetration and more frequent IPV perpetration at follow-up. Only PPCSs significantly predicted IPV perpetration after controlling for common predictors of IPV perpetration. Neither probably TBI nor PPCSs predicted frequency of IPV perpetration. Conclusion: When considered alongside common risk factors for IPV perpetration, PPCS was uniquely associated with the likelihood of IPV perpetration in this veteran sample. Given post-9/11 veterans' elevated risk for head injury, findings emphasize the distinctive value of PPCSs in understanding risk for IPV perpetration. We recommend increased assessment for PPCSs in clinical practice among veterans enrolled in VA care and highlight several important areas for future research and intervention development.